Recreational activities and interests of fourth year students of the provincial high schools in the division of Bulacan and their implications to health education - Ignacio, Sylvia (Gonzales) 1938- (Quezon City University of the Philippines, 1972)
The recreational activities and recreational interests of the fourth year students of the provincial high schools in the Division of Bulacan were studied.
Thesis (M.A.T. Health)--University of the Philippines.
Keywords: Health education -- Bulacan (Province).